Productive response of the Japanese quail (Coturnix coturnix japonica) to different natural growth promoters in the breeding and development stage - Bonifaz Ramos, Verónica de los Ángeles (2024)
This study evaluated the productive response of Japanese quail (Coturnix coturnix japonica) to natural growth promoters during male breeding and development stages. A completely randomized design was used with three treatments and a control group, each with three replicates, totaling 15 experimental units and 180 birds, starting at 8 days old for a duration of 7 weeks. The treatments were: T0 (Commercial Feed + Water ad libitum); T1 (Commercial Feed + 10 g Ginger/kg feed + Water ad libitum); T2 (Commercial Feed + 10 g Cinnamon/kg feed + Water ad libitum); and T3 (Commercial Feed + 10 g Oregano/kg feed + Water ad libitum). Variables measured included initial weight, final weight, weight gain, feed intake, feed conversion ratio, carcass yield, mortality, and cost-benefit ratio. Data were analyzed using Tukey's test at P<0.0005. T1 showed the best results with a final weight of 149.76 g, weight gain of 129.50 g, and a cost-benefit ratio of $2.74. T2 followed with a final weight of 139.74 g, weight gain of 120.69 g, and a cost-benefit ratio of $2.27. T3 had similar outcomes to T2, with a final weight of 138.6 g, weight gain of 118.45 g, and a cost-benefit ratio of $2.25. The control group, T0, recorded the lowest performance, with a final weight of 105.8 g, weight gain of 85.32 g, and a cost-benefit ratio of $2.2. These results suggest that natural growth promoters, especially ginger, significantly improve the productive performance and economic efficiency of Japanese quail during their growth stages.